Analysis of water polo injuries during 8904 player matches at FINA World Championships and Olympic games to make the sport safer - Mountjoy, M.; Miller, J.; Junge, A. (British Journal of Sports Medicine, 2019)
Objective To analyse injuries of water polo players reported during four Summer Olympic Games (2004, 2008, 2012, 2016) and four Federation Internationale de Natation World Championships (2009, 2013, 2015, 2017).